2020
DOI: 10.3390/microorganisms8081201
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania Immunity: Advancing Immunotherapy and Vaccine Development

Abstract: Parasitic diseases still constitute a major global health problem affecting billions of people around the world. These diseases are capable of becoming chronic and result in high morbidity and mortality. Worldwide, millions of people die each year from parasitic diseases, with the bulk of those deaths resulting from parasitic protozoan infections. Leishmaniasis, which is a disease caused by over 20 species of the protozoan parasite belonging to the genus Leishmania, is an important neglected disease. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 123 publications
(172 reference statements)
0
29
0
Order By: Relevance
“…Advanced tools based on bioinformatics and immunoinformatic methods are used to develop and design a vaccine that reduces the negative aspects of empirical methods, including preventing predictable ethical aspects of laboratory works and expensive experimental studies and being time consuming. In order to control VL, it is essential to stimulate both humoral and particularly cellular immune responses (Poland and Oberg 2010 ; Ghorbani and Farhoudi 2018 ; Farhani et al 2019 ; Ahmadi et al 2020 ; Ikeogu, Akaluka et al 2020 ; Mahboobi, Sedighian et al 2020 ; Oli, Obialor et al 2020 ). The humoral immune response, providing antibodies, is an essential part of the design of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced tools based on bioinformatics and immunoinformatic methods are used to develop and design a vaccine that reduces the negative aspects of empirical methods, including preventing predictable ethical aspects of laboratory works and expensive experimental studies and being time consuming. In order to control VL, it is essential to stimulate both humoral and particularly cellular immune responses (Poland and Oberg 2010 ; Ghorbani and Farhoudi 2018 ; Farhani et al 2019 ; Ahmadi et al 2020 ; Ikeogu, Akaluka et al 2020 ; Mahboobi, Sedighian et al 2020 ; Oli, Obialor et al 2020 ). The humoral immune response, providing antibodies, is an essential part of the design of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study demonstrated that L. donovani can directly activate B cells via endosomal TLR stimulation, proposing a novel parasite-driven survival mechanism by inducing hypergammaglobulinemia and increased levels of type I interferons, both associated with immune suppression and disease pathology (75) (Figure 2D). This study highlights the potential role B cells play in exacerbating disease, but this is still controversial, as both pathogenic and protective roles of B cells to other forms of Leishmaniasis have been described (72). Antibodies and serum are not protective against leishmaniasis (73,76), and when donor CD4 + T cells are transferred into irradiated Balb/c mice lacking B cells, they become resistant to Leishmania tropica infection (77).…”
Section: Visualizing Leishmania Infection Of the Livermentioning
confidence: 99%
“…B cell responses are considered to play a minor role in anti- Leishmania immunity and have been mostly studied in the context of cutaneous leishmaniasis in vivo ( 72 , 73 ). However, in visceral leishmaniasis, Moore et al demonstrated that highly motile B cells are present in L. donovani granulomas in the liver, irrespective of their antigen specificity or their capacity to interact with the intra-granuloma T cells ( 74 ).…”
Section: Visualizing Leishmania Infection Of the Livermentioning
confidence: 99%
“…A paramount public health concern, it is endemic in 98 countries. Approximately 2 million new cases are registered annually, with about 50,000 deaths each year [ 3 ]. Two epidemiological forms, cutaneous and visceral leishmaniasis, are diffuse in Algeria, which has the second-highest prevalence of cutaneous leishmaniasis ranks, after Afghanistan [ 4 ].…”
Section: Introductionmentioning
confidence: 99%